Does cranial ultrasound imaging identify arterial cerebral infarction in term neonates?. Issue 3 (21st April 2005) - Cowan, F; Mercuri, E; Groenendaal, F; Bassi, L; Ricci, D; Rutherford, M; de Vries, L
Abstract : Objective: To evaluate the diagnostic accuracy of cranial ultrasound (CUS) for detection of neonatal arterial territory cerebral infarction in term infants. Methods: CUS scans from term infants with neonatal magnetic resonance imaging (MRI) evidence of neonatal infarction were reviewed. The scans were grouped by acquisition time after birth: 1–3 days (early) or 4–14 days (late). Results: Brain MRI showed infarction in the territory of the middle cerebral artery in 43 of 47 infants, anterior cerebral artery in one, and posterior cerebral artery in three. Twelve of the 47 had minor changes on MRI in the white matter in the contralateral hemisphere, and four infants had bilateral infarctions. The early CUS scans were abnormal in 68% of the infants; the late CUS scans were abnormal in 87%. The late CUS scans were correct for laterality and site of lesion in 25/47 (53%) infants. In six infants with smaller lesions of the cortical middle cerebral artery branch or lesions in the posterior cerebral artery territory, the CUS scans were persistently normal. Conclusion: Normal early CUS scans do not exclude a diagnosis of neonatal stroke, although most scans are abnormal. CUS scans performed after day 3 were abnormal in 87% of infants. CUS scan findings were accurate for lesion laterality and site in 53%, and, in 34%, the scans showed abnormality strongly suggestive of infarction but not always site specific. For optimal prognostic information, infants with clinical histories or CUS scan findings suggestive of infarction should have a neonatal brain MRI scan.